Preparation and characterisation of gallium releasing 3-D alginate coated 45S5 Bioglass® based scaffolds for bone tissue engineering - Mourino, Viviana; Newby, Phillipa; Boccaccini, Aldo R. (Advanced Engineering Materials, 2010)
The aim of this work was to develop functional three-dimensional scaffolds based on Bioglass® derived glass-ceramics for bone tissue engineering (TE) with prophylaxis effect against infections. The highly porous scaffolds were fabricated by the foam replication technique and then coated with sodium alginate crosslinked with Ga3+. It was confirmed that the polymer coating did not affect the interconnectivity of the scaffold pore structure. The resulting composite scaffold exhibited antibacterial effect and improved mechanical properties as well as high bioactivity. The novel Ga3p loaded 45S5 Bioglass1-based scaffolds coated with alginate are promising candidates for bone TE applications. © 2010 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
UnivIS-Import:2015-03-09:Pub.2010.tech.IW.LM.prepar